2022
DOI: 10.3390/cells11152415
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk between Biomolecular Condensates and Proteostasis

Abstract: Proper homeostasis of the proteome, referred to as proteostasis, is maintained by chaperone-dependent refolding of misfolded proteins and by protein degradation via the ubiquitin-proteasome system and the autophagic machinery. This review will discuss a crosstalk between biomolecular condensates and proteostasis, whereby the crowding of proteostasis factors into macromolecular assemblies is often established by phase separation of membraneless biomolecular condensates. Specifically, ubiquitin and other posttra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 109 publications
1
4
0
Order By: Relevance
“…The “free” 20S CPs are nuclear even under osmotic stress, although they do not form the classical condensate granules of the 26S proteasome. It has been reported that RAD23B, a ubiquitin-binding shuttle protein, is essential in the formation of nuclear proteasomal condensates [ 21 , 33 , 36 ]. The p62/SQSTM1 ubiquitin-binding protein is another ubiquitin shuttle protein regulating nuclear condensates [ 33 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The “free” 20S CPs are nuclear even under osmotic stress, although they do not form the classical condensate granules of the 26S proteasome. It has been reported that RAD23B, a ubiquitin-binding shuttle protein, is essential in the formation of nuclear proteasomal condensates [ 21 , 33 , 36 ]. The p62/SQSTM1 ubiquitin-binding protein is another ubiquitin shuttle protein regulating nuclear condensates [ 33 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The UPS system is strongly associated with regulating biomolecular condensation ( 60 ). More specifically, ubiquitin and other post-translational modifications act as agents of phase separation, and are essential for the formation of condensates and ubiquitin-proteasome system activity ( 5 ). It is noteworthy that previous studies demonstrated that polyubiquitin chains can function as multivalent molecules that can drive either the assembly or the disassembly of condensates via interactions with various ubiquitin-binding proteins ( 72 , 73 ).…”
Section: Hypoxia-induced Protein Aggregation and Regulatory Responsesmentioning
confidence: 99%
“…However, these two types of higher-order protein assemblers are not completely independent. Disruptions in protein homeostasis under pressure or under pathological conditions can result in an imbalance of biomolecular condensation, ultimately leading to the uncontrolled collapse of these structures, which in turn triggers the irreversible aggregation and misfolding of protein constituents, and often leads to the transformation of aged or solidified condensates into aggregates ( 4 , 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, proteasomes and related marker proteins such as p62/SQSTM1 also recruit into LLPS. This process improves the efficiency of proteasomes and autolysosomes to clear misfolded proteins [41,42].…”
Section: Protein Aggregation Caused By Losing Of Proteostasismentioning
confidence: 99%